2018
DOI: 10.1302/1863-2548.12.170144
|View full text |Cite
|
Sign up to set email alerts
|

Postponing surgery of paediatric supracondylar humerus fractures to office hours increases consultant attendance in operations and saves operative room time

Abstract: PurposeTo assess if postponing surgery of paediatric supracondylar humerus fractures (SCHF) without compromised blood circulation to office hours can improve the quality of reduction and pin fixation and decrease complications.MethodsIn 2004, night-time (0am to 7am) surgery was allowed only for children with compromised blood circulation. Number of open reductions, surgeons experience, operation time, quality of reduction (Baumann angle, anterior humeral line crossing point with capitellum) and pin fixation as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 19 publications
0
8
0
2
Order By: Relevance
“…All six articles articles retrospectively compared postoperative outcomes of pediatric patients who had surgery for supracondylar humerus fractures at different times of the day. Primary outcomes in the studies were reduction quality [ 14 , 15 , 16 , 17 , 18 , 19 ], malunion rate [ 15 ], loss of reduction [ 17 ] and complications [ 16 ]. Also, functional outcomes in follow-up were assessed in three articles [ 14 , 15 , 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All six articles articles retrospectively compared postoperative outcomes of pediatric patients who had surgery for supracondylar humerus fractures at different times of the day. Primary outcomes in the studies were reduction quality [ 14 , 15 , 16 , 17 , 18 , 19 ], malunion rate [ 15 ], loss of reduction [ 17 ] and complications [ 16 ]. Also, functional outcomes in follow-up were assessed in three articles [ 14 , 15 , 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…Tuomilehto et al [ 19 ] assessed 200 fractures (mean age 7.1 years, range 1.8 to 14.1, 15.5% Gartland type II, 83.5% Gartland type III). Of these fractures, timing of surgery for the first 100 patients depended on circumstances, and could therefore be during the night (24:00–7:00) (12% of surgeries).…”
Section: Resultsmentioning
confidence: 99%
“…Zwei Arbeiten aus dem Jahr 2018 erschienen in The Bone & Joint Journal und Journal of Pediatric Orthopedic weisen darauf hin, dass die verzögerte Versorgung keine schlechteren Ergebnisse aufweist -natürlich unter Einbeziehung einiger Limitationen und auch der Tatsache, dass all diese Studien nicht prospektiv und/oder in genügend großen Populationen durchgeführt wurden. Es wird hervorgehoben, dass das Ausmaß der Expertise des Behandlers tagsüber deutlich besser ist [14,15], was am Ende einen Vorteil für den Patient darstellt. Die Operation sollte am der Indikationsstellung folgenden Tag als Erste geplant werden.…”
Section: Zeitpunkt Der Operativen Versorgungunclassified
“…Tage als feste Medikation und anschließend nach Bedarf. In einer Studie (Januar 2019) mit 81 Patienten, veröffentlicht in The Journal of Bone & Joint Surgery konnte gezeigt werden, dass die betreffenden Kinder meist nach 3 Tagen schmerzfrei sind und fast keine Schmerzmittel mehr benötigen[19,20]. Einer kontinuierlichen Therapie wird der Vorzug gegeben, um Schmerzspitzen zu vermeiden.Die Studie und eigene klinische Erfahrung weisen darauf hin, dass "outliners", die einen besonders hohen Schmerzmittelbedarf haben, ein Indiz dafür sein können, dass sich hinter einem hohen Schmerzmittelbedarf Komplikationen wie ein Kompartmentsyndrom oder eine Ischämie verstecken können.…”
unclassified
“…Operating the pediatric SHF patients within working or non-working hours is still debating in the literature. In recent studies, mal-union rates were reported to be higher in pediatric SHFs operated in the night hour surgeries and mean operative duration was found to be shorter in daytime surgeries [ 6 , 7 ]. On the other hand, in a recent article, there was no difference in reduction quality, complications and outcomes between pediatric SHF patients operated during the night or the daytime [ 8 ].…”
Section: Introductionmentioning
confidence: 99%